2021
DOI: 10.3389/fonc.2021.634851
|View full text |Cite
|
Sign up to set email alerts
|

Sophoridine Inhibits the Tumour Growth of Non-Small Lung Cancer by Inducing Macrophages M1 Polarisation via MAPK-Mediated Inflammatory Pathway

Abstract: Lung cancer is one of the most common and lethal neoplasms for which very few efficacious treatments are currently available. M1-like polarised tumour-associated macrophages (TAMs) are key mediators to modulate the tumour microenvironment, which play a key role in inhibiting cancer cell growth. Sophoridine, a naturally occurring alkaloid, exerts multiple pharmacological activities including anti-tumour and anti-inflammatory activities, but it has not been characterised as a regulator of tumour microenvironment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Lung cancer cells recruit monocytes, neutrophils, and other WBCs by secreting various mediators, thereby producing a series of inflammatory factors [ 25 ]. Reactive oxygen species (ROS), the oxidative product of cell metabolism, damages lipid, nucleic acid, and protein function, breaks the oxidative balance, induces oxidative stress, and promotes inflammation, all of which lead to various diseases [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lung cancer cells recruit monocytes, neutrophils, and other WBCs by secreting various mediators, thereby producing a series of inflammatory factors [ 25 ]. Reactive oxygen species (ROS), the oxidative product of cell metabolism, damages lipid, nucleic acid, and protein function, breaks the oxidative balance, induces oxidative stress, and promotes inflammation, all of which lead to various diseases [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, reprogramming of M2-like macrophage toward the antitumoral might be potential new therapeutic targets. More and more studies have indicated the mechanism of monomeric components of traditional Chinese medicine exert anti-tumor effect by modulating M1 or M2 macrophage polarization [33,34].…”
Section: Discussionmentioning
confidence: 99%
“… 24 In Lewis mouse model, Zhao et al (2014) found that sophoridine (15 and 25 mg/kg) effectively inhibits tumor growth of non-small lung cancer by activating MAPKs signaling pathway and increasing expression of pro-inflammatory cytokines and M1 surface marker CD86. 25 …”
Section: Pharmacological Activities Of Sophoridinementioning
confidence: 99%
“…24 In Lewis mouse model, Zhao et al (2014) found that sophoridine (15 and 25 mg/kg) effectively inhibits tumor growth of non-small lung cancer by activating MAPKs signaling pathway and increasing expression of pro-inflammatory cytokines and M1 surface marker CD86. 25 Dong et al (2014) assessment of these properties revealed that mesoporous silica nanospheres effectively regulated the uptake and release of sophoridine; however, how these nanospheres perform in vivo remains unknown. 26 Inspired by the above ideas, Wang et al (2016) prepared sophoridine-loaded PLGA microspheres using the O/O emulsion-solvent evaporation method, which exhibited combined lung-targeting and sustained drug release properties.…”
Section: Anti-stomach Cancer Cellsmentioning
confidence: 99%